Air Pollution in Asia and Its Effect on Human Health: Air Pollution in Asia - Gezerman, Ahmet Ozan; Corbacioglu, Burcu Didem (IGI GLOBAL, 2018)
Although continuous efforts to monitor and mitigate air pollution are being made, it is still prevalent in most countries in the world. Major contributors include fossil fuel exhaust in metropolitan cities from industrial facilities and vehicular emissions. Use of renewable energy and natural gas have played a part in reducing air pollution; however, increasing populations, rampant urbanization, and industrialization, especially during winter months, have given rise to spikes in air pollution levels. Research shows that there is a close relationship between air pollution and mortality rates depending on respiration inadequacy. Studies show that contaminants increase respiratory afflictions in humans. Discontinuing use of fossil fuels, using appropriate burning techniques, and efficiency emission controls on vehicles have been proven to reduce air pollution levels.
Keywords: DIESEL EXHAUST PARTICLES; NONATOPIC NONASTHMATIC SUBJECTS; BRONCHIAL EPITHELIAL-CELLS; ATOPIC ASTHMATIC-PATIENTS; NITROGEN-DIOXIDE; OZONE; EXPOSURE; RELEASE; IMPACT; Science & Technology - Other Topics; Engineering; Public, Environmental & Occupational Health